Vključevanje prostorskega in okoljskega vidika v regionalne razvojne programe v programskem obdobju 2007-2013 - Gulič, Andrej (Urbani izziv, 2005)
The article presents analyses of integration of spatial and environmental aspects in documents concerning development planning, regional structural policy and physical and environmental planning on the national, regional and local level. These are followed with guidelines for amending the system of development planning and integration of physical and environmental aspects into the new generation of regional development programmes. Possibilities for linking regional development programmes and regional concepts of spatial development are also presented.
Keywords: ecology; ekologija; prostorski razvoj; prostorsko planiranje; razvojni programi; regionalna politika; regionalni razvoj; regionalno planiranje; Slovenia; Slovenija; spatial planning